"Walls within walls: examining the variegated purposes for walling in Ghanaian gated communities". Issue 4 (21st April 2023) - Ehwi, Richmond Juvenile
Abstract: This paper examines the functions walls perform in gated communities from the standpoints of both gated community developers and their residents. It posits three types of walls and scrutinises the purpose for each. Drawing empirical data from face-to-face interviews with 11 developers and 20 residents drawn from two gated communities in the Greater Accra Metropolitan Area in Ghana, the paper finds that, contrary to received wisdom, internal cluster walls in gated communities are used to segregate residents into different economic and social classes, often under the pretext of offering them different housing choices. It further casts doubts on the widely touted view that gated communities offer a better sense of security as residents express anxieties over suspected criminals living among them. The paper concludes by calling for a re-examination of several features of gated communities, including the meaning of the concept itself and the typologies that exist to bring out more of such nuances.